Liquid nitrogen cooling, control and monitoring system for the ELIADE HPGe clover detectors at ELI-NP. (1st July 2022) - Dhal, A.; Ramirez, F.; Suliman, G.; Roman, T.; Ciocan, G.; Testov, D.; Petcu, C.; Tatulea, B.; Ur, C.A.; Balabanski, D.L.
Abstract: We present a liquid nitrogen (LN2 ) cooling station for the high-purity germanium (HPGe) segmented clover detectors of the ELI-NP Array of DEtectors (ELIADE) spectrometer, including its associated filling control and monitoring systems, all designed and built in-house at Extreme Light Infrastructure - Nuclear Physics (ELI-NP), Măgurele, Romania. The automated LN2 filling process is controlled by a CompactRIO (cRIO) system from National Instruments through a custom LabVIEW software used for monitoring both the internal germanium crystal temperatures as well as the temperatures of external Pt100 sensors (used for detection of overflow of LN2 from detectors during a filling process). The detectors are filled with LN2 by opening their individual filling valves (which are mounted on the cooling station) and the process is automatically stopped once an overflow condition is fulfilled by the corresponding external Pt100 sensor located downstream. A twelve-hour cycle is used to periodically fill all of the detector dewars and keep their germanium crystals cool at all times. The associated Graphic User Interface (GUI), Command Line Interface (CLI) and Text User Interface (TUI) are used for both controlling and monitoring the above mentioned process. Alert and warning email messages were also enabled via the cRIO system so that users can be alerted in real-time in the event of any cooling malfunction. In this way, any issues related to the cyclic filling procedure, as well as any abnormal observations regarding the germanium crystal temperatures can be quickly and efficiently addressed before the detectors have a chance to warm back up to room temperature. Temperature data of all the Pt100 sensors corresponding to detectors as well as to the solenoid valves are made available in an influx database by the cRIO control system. The web application Grafana access the database and plots them in real-time for online monitoring.